2004
DOI: 10.1088/0953-8984/16/20/018
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigations of the microscopic spin Hamiltonian parameters including the spin–spin and spin–other-orbit interactions for Ni2+(3d8) ions in trigonal crystal fields

Abstract: The microscopic origin of the spin Hamiltonian (SH) parameters for Ni 2+ (3d 8 ) ions in a trigonal type I symmetry (C 3v , D 3d , D 3 ) crystal field (CF) is studied. In addition to the spin-orbit (SO) interaction, we consider also the spin-spin (SS) and spin-other-orbit (SOO) interactions. The relative importance of the four (SO, SS, SOO, and combined SO-SS-SOO) contributions to the SH parameters is investigated using the CFA/MSH package and the complete diagonalization method (CDM). The SO mechanism is domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 20 publications
1
74
0
Order By: Relevance
“…The origin of the fine structure as resulting "from the crystal field and the spin-spin interactions" is not quite correct since as recent microscopic spin Hamiltonian studies [73,74] reveal the spin-orbit interactions contribute dominantly to ZFS, whereas the contribution from the spin-spin interactions is rather minor. The determination of the direction cosines of the distortion axis using the method of Rao and Subramanian [75] used in [72] appears to be valid only for the cases of axial distortions of sixfold nearly cubic ML 6 complexes.…”
Section: G 'The Rhombic Component Of the Crystal Fields Around The Mmentioning
confidence: 99%
“…The origin of the fine structure as resulting "from the crystal field and the spin-spin interactions" is not quite correct since as recent microscopic spin Hamiltonian studies [73,74] reveal the spin-orbit interactions contribute dominantly to ZFS, whereas the contribution from the spin-spin interactions is rather minor. The determination of the direction cosines of the distortion axis using the method of Rao and Subramanian [75] used in [72] appears to be valid only for the cases of axial distortions of sixfold nearly cubic ML 6 complexes.…”
Section: G 'The Rhombic Component Of the Crystal Fields Around The Mmentioning
confidence: 99%
“…(3d 8 ) ions in some crystals [13,[18][19][20]. They found that, for 3d 2 and 3d 8 ions at trigonal symmetry sites, although the SO mechanism is the most important one, the SS and SOO interactions were found important.…”
Section: +mentioning
confidence: 99%
“…By taking into account the SS and SOO interactions, the total Hamiltonian of a 3d 2(8) ion in trigonal crys- * corresponding author; e-mail: weiaqun@163.com tal field (CF) in intermediate scheme can be written as [13,[18][19][20]: [23,26], and hence play a key role in the CF studies.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…where B kl are the CF parameters in Wybourne notation [31,32].Ā k (R) (k = 2, 4) are the intrinsic parameters. For 4d n ions in crystals, the ratiō A 2 (R)/Ā 4 (R) ≈ 6 ± 2 was found [29, n clusters is about 1.5(1) times that of the isoelectronic 3d n clusters [19].…”
Section: Calculationmentioning
confidence: 99%